Moving Boundary: A Virtual Museum of the Ethnic Groups: This museum doesn’t exist in the real life, we will create it together - Karadecheva, Maria (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2012)
The virtual museum of ethnic groups “Moving boundary” is a prop osition for dialogue on an important topic in today’s world – ethnic coexistence. The project’s goal is to make various resources (photos, documents, etc.) available for use by teachers, professors and students, thus forming and strengthening connections between educational institutions.